EVALUASI PENGENDALIAN DAN OPERASI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN DALAM MENANGGULANGI KEBAKARAN PADA TAHUN 2022 - 2023 DI KOTA PEKANBARU - Erfan, Rabbil; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Fire and Rescue Department (DPKP) of Pekanbaru City plays a crucial role in fire prevention and protecting the public from fire-related risks. This study aims to evaluate the effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy in the implementation of DPKP’s duties during the 2022–2023 period. The research employs a descriptive qualitative method with an evaluative approach, using primary data obtained through interviews with DPKP officers and community members, as well as secondary data from annual reports and relevant documents. The results indicate that although DPKP has performed its duties fairly well, several challenges remain. In terms of effectiveness and responsiveness, limitations in personnel and equipment have led to delayed response times, and fire safety education remains insufficient. Regarding efficiency, the budget allocation is still heavily focused on fire suppression rather than prevention, leading to suboptimal outcomes. In terms of adequacy, the number of fire stations, vehicles, and personnel does not yet meet ideal standards. Service distribution is also uneven, particularly in areas with limited accessibility. Furthermore, the accuracy of policies and procedures still requires alignment with field conditions through better inter-agency coordination. Based on these findings, it is recommended that DPKP increase the number of fire stations, optimize budget allocation for prevention efforts, expand public education programs, and improve coordination systems with relevant agencies. These steps are expected to enhance the effectiveness and quality of DPKP's services in combating fires and mitigating their impact on the community. Keywords: Evaluation, Fire Department, Fire Incident, Effectiveness, Responsiveness, Optimal.